Exploring Selfhood through Performance in The Danish Girl. (November 2018) - Dowerah, Swikrita; Nath, Debarshi Prasad
The Danish Girl presents the life history of a transgender person in early twentieth century Denmark and is remarkable for its use of visual codes to broach important questions on human subjectivity. The article probes deep into the social structure that frames subjectivity and questions the very idea of the symbolic. It looks at how the filmmaker makes use of cinematic elements as well as various codes and tropes provided to him by psychoanalysis, to critique the conventional understanding of phallic power. Grounded on the established domains of gender theorization, the article is therefore an interpretative analysis of the film that attempts to subvert these very discourses that frame our understanding of gender performance.